2022
DOI: 10.37148/comphijournal.v3i2.99
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Stress, Keteraturan Pola Makan dan Konsumsi Bahan Pangan Iritatif Terhadap Kejadian Dyspepsia

Abstract: Stress, regular diet, and consumption of irritating food are some of the risk factors for dyspepsia. Medical students at the first level undergo a fairly high density of activities, where this requires an adaptation process that can cause stress. In stressful conditions, the regularity of eating patterns is disrupted. There are also many incidents of students consuming irritating foodstuffs.Aims of researchto analyze stress factors, regularity of eating patterns and consumption of irritating foodstuffs onthe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Irritative foods can interfere with the digestive system, especially the stomach and intestines, if consumed too much. (Rusmanto et al, 2022). The results showed that the majority of students had a negative history of consuming NSAIDs, as many as 126 students (85.7%).…”
Section: Functional Dyspepsia and Factors Associated With Functional ...mentioning
confidence: 94%
See 1 more Smart Citation
“…Irritative foods can interfere with the digestive system, especially the stomach and intestines, if consumed too much. (Rusmanto et al, 2022). The results showed that the majority of students had a negative history of consuming NSAIDs, as many as 126 students (85.7%).…”
Section: Functional Dyspepsia and Factors Associated With Functional ...mentioning
confidence: 94%
“…The irritative eating pattern of the respondents found that 133 respondents with a nonirritative diet pattern were 133 respondents (90.5%). Research conducted by Rusmanto et al (2022) on students of the Faculty of Medicine, University of Muhammadiyah Malang, that found that the majority of respondents, as many as 36 people (60%) did not eat irritating foods. Irritative foods can interfere with the digestive system, especially the stomach and intestines, if consumed too much.…”
Section: Functional Dyspepsia and Factors Associated With Functional ...mentioning
confidence: 99%
“…Sejalan dengan hasil penelitian Rusmanto et al, (2022) bahwa kejadian dyspepsia dipengaruhi oleh pola makan dengan nilai p-value 0,022. Didukung hasil penelitian Octaviana et al, (2021) bahwa terdapat hubungan pola makan dengan kejadian dyspepsia dengan nilai p-value 0,001.…”
Section: Issn 2252-3624 E-issn 2988-7062unclassified